Magyar-román kiadatási tárgyalások és eljárások háborús bűnösök ügyeiben a II. világháború után - Kovács, Szabolcs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
This study examines the operation of the Cluj People’s Tribunal in the years following the Second World War, with particular emphasis on the legal and political context of the extradition agreements concluded between Romania and Hungary. The analysis situates the tribunal’s judicial practices within the broader international and regional efforts to prosecute war criminals, highlighting how diplomatic cooperation between the two states – along with its inherent limitations – shaped the outcomes of individual proceedings. The study addresses the jurisdictional disputes arising from the implementation of the extradition agreements, the challenges related to the transfer and evaluation of evidence, and the ways in which these processes reflected the ethnopolitical tensions present within Romanian justice system. Through a comparative examination of sources, the study argues that the functioning of the Cluj People’s Tribunal was defined by the dual aims of post-war transitional justice: the pursuit of accountability and the reinforcement of political legitimacy. This duality significantly influenced Romanian – Hungarian extradition practices and played a key role in shaping the region’s post-war legal and memory politics.